Plasmafiltration as an effective method in the removal of circulating pegylated liposomal doxorubicin (PLD) and the reduction of mucocutaneous toxicity during the treatment of advanced platinum-resistant ovarian cancer - Kubeček, Ondřej; Martínková, Jiřina; Chládek, Jaroslav; Bláha, Milan; Maláková, Jana; Hodek, Miroslav; Špaček, Jiří; Filip, Stanislav (Cancer chemotherapy and pharmacology, 2020)
PURPOSE: The present study evaluates the safety and efficacy of double-plasma filtration (PF) to remove the exceeding pegylated liposomal doxorubicin (PLD) in circulation, thus reducing mucocutaneous toxicity. METHODS: A total of 16 patients with platinum-resistant ovarian cancer were treated with 50 mg/m2 PLD applied in 1-h IV infusion every 28 days. PF was scheduled at 44-46 h post-infusion. The concentration of plasma PLD and non-liposomal doxorubicin (NLD) was monitored with high-performance liquid chromatography at 116 h post-infusion. A non-linear method for mixed-effects was used in the population pharmacokinetic model. The dose fraction of PLD eliminated by the patient prior to PF was compared with the fraction removed by PF. PLD-related toxicity was recorded according to CTCAE v4.0 criteria and compared to historical data. Anticancer effects were evaluated according to RECIST 1.1 criteria. RESULTS: The patients received a median of 3 (2-6) chemotherapy cycles. A total of 53 cycles with PF were evaluated, which removed 31% (10) of the dose; on the other hand, the fraction eliminated prior to PF was of 34% (7). Exposure to NLD reached only 10% of exposure to the parent PLD. PLD-related toxicity was low, finding only one case of grade 3 hand-foot syndrome (6.7%) and grade 1 mucositis (6.7%). Other adverse effects were also mild (grade 1-2). PF-related adverse effects were low (7%). Median progression-free survival (PFS) and overall survival (OS) was of 3.6 (1.5-8.1) and 7.5 (1.7-26.7) months, respectively. Furthermore, 33% of the patients achieved stable disease (SD), whereas that 67% progressed. CONCLUSION: PF can be considered as safe and effective for the extracorporeal removal of PLD, resulting in a lower incidence of mucocutaneous toxicity.
Keywords: doxorubicin; lidé; Middle Aged; Adult; Ovarian Neoplasms; EPR effect; prospektivní studie; Antibiotics, Antineoplastic; Female; Doxorubicin; Population kinetics; Humans; nádory vaječníků; Organoplatinum Compounds; protinádorová antibiotika; Polyethylene Glycols; Prospective Studies; Hand–foot syndrome; polyethylenglykoly; lidé středního věku; Drug-Related Side Effects and Adverse Reactions; Cancer therapy; ženské pohlaví; organoplatinové sloučeniny; Pegylated liposomal doxorubicin (PLD); Mucocutaneous toxicity; Aged; nežádoucí účinky léčiv; Ovarian cancer; dospělí; Plasmapheresis; senioři